Sharing Resource Wealth Inclusively Within and Across Generations - Pouokam, Nathalie (Washington, D.C. : International Monetary Fund, 2021)
This paper discusses the main challenges faced by resource-rich nations in promoting equity; describes policy tools available for managing exhaustible natural resources; and analyzes the relationship between resource wealth and state fragility. It is argued that human capital accumulation, innovation, and technology diffusion can help escape the trap of low growth and resource dependence that plagues so many developing countries. But to make this possible, resource-rich nations must sustain strong citizen participation in the policy making to hold governments accountable and ensure the inclusive management of resource wealth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Agricultural and Natural Resource Economics; Environmental and Ecological Economics; Foreign Exchange; Informal Economy; Underground Econom